Probing the self-defining period in memories of the Bangladesh independence war generation. Issue 10 (26th November 2021) - Islam, Azharul; Haque, Shamsul
ABSTRACT: This study investigated the self-defining periods (SPs) in private and public memories of Bangladeshi older adults ( N = 476; mean age = 67.16 years) who, during adolescence and early adulthood, witnessed the 1960s Bengali nationalist movement and the 1971 Bangladesh War of Independence. Each participant retrieved three private and three public memories they considered to be highly significant. The lifespan distributions for private and public memories were identical; in both cases, participants recalled more than half of their memories from 10 to 29 years of age. The calendar-year distributions revealed that nearly one-fourth of private and one-third of public memories were recalled from the year of the War of Independence. The memory content analysis showed that participants sampled more negative than positive memories: 55% versus 45% for private memory and 66% versus 34% for public memory. The enhanced recollection of private and public memories from 10 to 29 years of age was predominantly shaped by memories of the independence struggle—a period that was self-defining for the entire Bangladeshi society.